Branding, websites and the importance of first impressions in the veterinary industry. Issue 4 (6th May 2022) - Phillips, Justin
Abstract : Technology has changed consumer behaviour, and this has led to new and exciting opportunities for veterinary practices to engage with, and attract, clients. But, in order to grab their attention, an effective brand and a well‐designed website, focused on conversions that generate revenue for your practice (ie, clients booking appointments and joining health plans, ordering repeat prescriptions or leaving reviews), are key. This article discusses the things to consider when conveying a practice's story to current and prospective clients, and explains how to give your brand the audience it deserves.